Implementing The Spirit of Jihad in Sufism - Meirison Meirison; M. Harir Muzakki (Jurnal Theologia, 2020)
This paper aims to illustrate that Sufism does not fully lead to scepticism and passivity in fighting for the benefit of Muslims. Sufism was originally a zuhud (ascetic) movement in Islam, and in its development, gave birth to the tradition of Islamic mysticism. Some Islamic thinkers argue that Sufism is an exile from the people who are more concerned with spiritual life so that they no longer think about the problems of Muslims. Sufism experts, as described the Sufis do not care about what is happening around them, let alone strive for the religion of Allah and also as defined by the public. This article is a literature study and uses the content analysis method from several documents about the history of Sufism. This paper proves that not all accusations about Sufism are true. It could see from the reality on the ground, and it turns out that the Sufis and their students play a lot of roles in helping the struggle of Muslims. Both in eradicating evil, re-implementing the Islamic Shari'a, abolishing polytheism, and Jihad. Jihad that has long been forgotten by Muslims in the late Ottoman period. The struggle of heroic Sufis will never fade from the pages of history. True Sufism is Sufism, which follows the instructions of Allah and His Messenger towards the cleanliness of the spirit, the glory of morals and manners, which finally knows Allah with bright eyes. The Holy Jihad is for the sake of perfection, Jihad against self, greed, against tyranny.